Open Studio: Ten Years : Open Studio Toronto 1980. Dedicated to Nick Novak 1954 - September 1980. - Heinrich, Theodore Allen; The Art Gallery at Harbourfront, Toronto (Toronto : Open Studio, 1980)
Altwerger, Sandra ; Andrews, Kim ; Benoît, Jacques ; Benson, Mel ; Carr, Don ; Clark, Moira ; Farquhar, Susan ; Feldman, Paul ; Funahashi, Zenji ; Game, Robert ; Gaucher, Yves ; Gouin, Judy ; Hague, Elizabeth ; Hall, Barbara ; Heimpel, Carol ; Holman, Don ; Jakovac, Nikolette ; etc.
Open Studio: Ten Years, Open Studio Toronto 1980, The Art Gallery at Harbourfront, Toronto, October 3 - November 2, 1980. Exhibition circulated by Art Gallery of Ontario Extension Services, 1981-1982
English
kunstcatalogus